Preparation and characterization of poly (hydroxamic acid) chelating resin for metal ions removal from water - Nur 'Atikah , Abdullah (2012)
Graft copolymerization of methyl acrylate (MA) onto kenaf cellulose was carried out using redox method in which ammonium ferrous sulphate was used as an initiator. The poly (methyl acrylate) grafted kenaf cellulose was obtained at 55 °C after 2 hours stirring, and purified acrylic polymer-grafted cellulose was characterized by FTIR and ICP-MS analysis. There in, the ester and nitrile functional groups of the grafted copolymers were reacted with hydroxylamine solution for conversion into the hydroxamic acid ligands. The chelating behavior of the prepared ligands toward some metal ions was investigated using batch technique. The adsorptions of metal ions onto ligands were dependent on pH parameter and the amount adsorbed towards metal ions following order: Zn2 > Fe 3 > Cr> Cu 2 > Ni2.